(untitled) - Thrush, Emily Austin (New York, 1997)
This text is designed to give students the opportunity to practice speaking and listening skills in a variety of contexts. While some activities encourage specific grammar structures, in general the activities are intended to promote fluency and improve communication skills. Designed for pre-beginning to beginning ESOL students.
Keywords: English language; Spoken english,Problems, exercises, etc